Debat Lintas Agama di YouTube sebagai Ruang Pembelajaran Agama Informal: Transformasi Otoritas Pendidikan Agama Islam di Era Digital - Ona Yulita; Rizki Hariandi; Diana Sari; Amir Syarifuddin; Supriadi; Umar Manshur; Mona Novita (IEC: Journal of Educational Innovation, 2026)
This study examines interfaith debate on YouTube as a form of informal religious learning and its implications for the transformation of Islamic religious education authority in the digital era. While Islamic religious education has traditionally been situated in formal institutions such as schools, madrasahs, and pesantren, digital platforms increasingly shape religious learning beyond formal pedagogical structures. This study analyzes how Muslim audiences engage with interfaith debate content, how learning experiences emerge, and how religious authority is negotiated in platform-mediated environments. This research employed an exploratory qualitative design combining digital observation, qualitative content analysis, and semi-structured interviews. Data were collected from 50 interfaith debate videos on YouTube, approximately 420 purposively selected audience comments, and interviews with 20 active Muslim viewers. Data were analyzed thematically using NVivo 14. The findings indicate that YouTube functions not only as a space for religious polemics but also as a potential informal learning environment where audiences compare arguments, seek clarification, reflect on beliefs, and independently explore religious issues. Perceptions of religious authority are increasingly negotiated through scholarly legitimacy, communicative performance, digital social validation, and algorithmic visibility. However, this pedagogical potential is ambivalent, as opportunities for reflective learning coexist with risks of confirmation bias, polarization, and performative religious consumption. The study concludes that Islamic religious education should expand its pedagogical orientation by strengthening digital religious literacy, ethical dialogue, and critical evaluation of religious authority in digital environments.